Determination of liver damage indices APRI and FIB-4 score in adolescents with juvenile idiopathic arthritis - L.A. Strashok; O.S. Pavlova (Zaslavsky O.Yu., 2020)
Background. Liver damage at the early stages of juvenile idiopathic arthritis treatment does not have a clear clinical picture. To identify children who need further liver examination, non-invasive diagnostic indexes can be used. The purpose was to study the possibility of using non-invasive liver damage indexes in adolescents with juvenile idiopathic arthritis. Materials and methods. Sixty-eight adolescents were examined: 25 boys (36.8 %) and 43 girls (63.2 %). The average age of the patients was 13.3 ± 0.3 years. All adolescents underwent laboratory and instrumental studies: clinical blood test and clinical analysis of urine, liver tests (total bilirubin and its fractions, cholesterol, β-lipoproteins, aspartate aminotransferase (AST), alanine aminotransferase (ALT)), hemorenal tests, acute phase indicators (C-reactive protein, antistreptolysin O, rheumatoid factor, antinuclear antibodies), abdominal ultrasound, joint ultrasound, electrocardiography and liver damage indexes - APRI and FIB-4 score. Results. We have found that the average levels of total bilirubin, AST, ALT did not exceed the laboratory norm. Average cholesterol levels were within normal limits in all groups. The average values of β-lipoproteins were increased in all groups of adolescents. According to our studies, 44 % of adolescents with juvenile idiopathic arthritis have signs of liver damage according to the results of an ultrasound even before methotrexate treatment. Conclusions. The obtained results confirm the significance of the studied indexes for identifying children who require careful liver monitoring during juvenile idiopathic arthritis treatment with methotrexate. It was found that the most appropriate is the comprehensive use of indexes and comparing them in dynamics.